Association between dietary diversity and risk of depressive symptoms in Chinese children, adolescents, and college students - Ren, Zhongyu; Gao, Liya; Hao, Zixuan; Zhao, Boyang; Li, Jin; Li, Guilin; Cao, Jianhua; Tang, Xuemei (Frontiers in Nutrition, 2026)
Background and objectiveChildhood, adolescence, and emerging adulthood represent critical transitional periods characterized by rapid biological, psychological, and social development, each of which may distinctly influence diet–mood interactions. To date, no study has concurrently examined the association between dietary diversity and depressive symptoms across the full developmental spectrum spanning these life stages. As a result, age-specific vulnerabilities and potential windows for intervention remain poorly understood. Using a large and diverse sample of Chinese children, adolescents, and university students, this cross-sectional study aimed to explore the relationship between dietary diversity and depressive symptoms across these key developmental periods. The findings may help inform the design of targeted, developmentally appropriate nutritional strategies for depression prevention.Materials and methodsIn this cross-sectional investigation, a total of 11,856 Chinese college students and 1,281 children and adolescents were enrolled. All participants completed self-administered questionnaires assessing demographic characteristics, lifestyle behaviors, dietary diversity, and depressive symptoms [evaluated with the Patient Health Questionnaire-9 (PHQ-9) and the 20-item Zung Self-Rating Depression Scale (SDS)]. Multivariable logistic regression analyses were employed to examine the associations between dietary diversity and depressive symptoms, with adjustment for relevant confounding factors.ResultsThe prevalence of depressive symptoms was 18.9% (2,245/11,856) among college students and 4.7% (60/1,281) among children and adolescents. Among college students, a significant inverse relationship was observed between dietary diversity scores and depressive symptoms. Compared to participants with a score of 0, the adjusted odds ratios decreased progressively with higher scores, ranging from OR = 0.94 (95% CI: 0.39, 2.30) for a score of 1 to OR = 0.33 (95% CI: 0.13, 0.81) for a score of 9. Similarly, among children and adolescents, higher dietary diversity was associated with markedly lower odds of depressive symptoms, with ORs declining from 0.164 (95% CI: 0.007, 3.837) for one food score to 0.026 (95% CI: 0.002, 0.390) for seven food scores, relative to the zero-score reference group. In analyses of specific food groups, college students showed significant inverse associations between depressive symptoms and consumption of vegetables (OR = 0.67, 95% CI: 0.55, 0.81), fruits (OR = 0.78, 95% CI: 0.70, 0.88), red meat (OR = 0.85, 95% CI: 0.75, 0.95), and soy products (OR = 0.89, 95% CI: 0.80, 0.99). Among children and adolescents, significant associations were observed for multiple dietary factors, with inverse associations for fruit intake (P = 0.019) and breakfast consumption (P < 0.001), and positive associations for sugar-sweetened beverages (P = 0.025), fried foods (P < 0.001), fast food (P < 0.001), and processed foods (P = 0.033).ConclusionsThis study establishes a significant inverse relationship between dietary diversity and depressive symptoms. The results support the integration of dietary diversity into public health recommendations and behavioral interventions. Specifically, fostering diverse and healthy eating patterns emerges as a promising, practical strategy for the prevention of depressive symptoms, underscoring the role of nutrition in mental well-being.